KARAKTERISTIK PEMAKAIAN BAHASA LARAS IKLAN PADA JEJARING SOSIAL INSTAGRAM (Kajian Sosiolinguistik) - DOMPAS, YETTY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research entitled Characteristic of Register Used in Advertisement on Instagram. Some problems that will be explained in this research are how is the characteristics of diction on advertisement on Instagram? And how is the code mixing on advertisement on Instagram? This research aimed to describe the characteristics of diction and code mixing on advertisement on Instagram. The method used in this research is observation method which observes the use of language on advertisement on Instagram. The technic used is a recording technic with a recorder, a smartphone, by taking pictures of advertisements posts on phones screen. The analyzing results of this research can be concluded as: the characteristics of diction showed on register used on advertisement on Instagram include : a) the used of foreign words, b) the use of slang words, c) the use of words with synonym, d) the use of special words, e) the use of idiom, f) the use of words or specific terms, and g) the use of dialectical words. The use of those words is based on type of products being advertised, listeners age, gender, and the desire of advertisers to bring message or information of their advertisement with communicative language, brings modern and impressive impression, and easy to be understood by listeners. The used of the seven characteristics of diction is caused by dictions mentioned above be able to perform advertising language on social media especially Instagram, which is easy to be understood by readers, according to the type of advertised product, and be able to convey advertisement’s messaging precise to the advertisement’s target. Code mixing appeared on Instagram include: a) code mixing form word, b) code mixing form phrase, c) code mixing form baster, and d) code mixing form clause. Keywords: Language used, register, Instagram.